1968
DOI: 10.1039/j29680000211
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of some 1-phenylpyrazole derivatives

Abstract: The steric effects of substituents and the position of protonation in strongly acidic media are discussed in terms of the changes observed in ultraviolet and n m r . absorption. A new series of 1 -pentafluorophenylpyrazoles has been synthesrsed, and their spectra are compared with those of the parent pyrazoles. Twenty-five commonly occurring bands in the infrared spectra of 1 -phenylpyrazoles are tabulated and assignments have been made.FURTHER to recent ultraviolet ( U . V . ) ~~ and nuclear magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…7). [172,173] It was found that these different approaches, as shown in Figure 6, lead to different coordination isomers, namely facial (fac) and meridional (mer) complexes (Fig. 8).…”
Section: Iridium(iii) Complexes With Three Cyclometalating Ligandsmentioning
confidence: 97%
See 1 more Smart Citation
“…7). [172,173] It was found that these different approaches, as shown in Figure 6, lead to different coordination isomers, namely facial (fac) and meridional (mer) complexes (Fig. 8).…”
Section: Iridium(iii) Complexes With Three Cyclometalating Ligandsmentioning
confidence: 97%
“…7). [172,173] In a contribution by Thompson and co-workers, different synthetic procedures for the preparation of iridium(III) triscomplexes containing heterocyclic phenylpyridine derivatives are discussed (Fig. 7).…”
Section: Iridium(iii) Complexes With Three Cyclometalating Ligandsmentioning
confidence: 99%
“…The ortho deshielding phenomenon and its disappearance in P-methyl derivatives has been noted previously in substituted phenylpyrazoles (6)(7)(8)(9) and also in 3-phenylpyridazines (lo), 2,2'-bipyridyl (4,5), and in aryl-triazines and tetrazines (3). The loss of the interaction has been ascribed to a loss of coplanarity between the rings (6-12) which causes a diminution of the anisotropic effects and a disruption of the resonance interaction.…”
Section: Arylazolesmentioning
confidence: 99%
“…Fraser and Haque (1) have reported the upfield shift in the meta-and para-protons (H,,,,,) of the phenyl ring and the accompanying downfield shift in the ortho protons (H,) on changing a methyl group from the 1-to the 2-position of a methyl substituted -5 -phenyltetrazole (compare compounds 5 and 10, Table 1). The overall effect relative to benzene is considered to arise from a combination of ring anisotropy, nitrogen anisotropy, and an electron donating resonance interaction between the rings in compound 10 which is absent or very small in compound 5 (1)(2)(3)(4)(5)(6)(7)(8)(9). A comparison (Table 1) shows that this is a general effect in the azoles.…”
Section: Arylazolesmentioning
confidence: 99%
See 1 more Smart Citation